APLIKASI METODE SENTRA PADA PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER ANAK USIA DINI - Winarti, Wiwin; Amirudin, Amirudin; Sitika, Achmad Junaedi (Universitas Pakuan, 2021)
APPLICATION OF THE CENTER METHOD IN THE LEARNING PROCESS OF ISLAMIC RELIGIOUS EDUCATION IN SHAPING EARLY CHILDHOOD CHARACTERSThe purpose of this study is to explore the impact of using the application of the center method in Islamic Religious Education learning on the formation of children's character. Fun parenting and education patterns for children can greatly contribute to shaping their character, so there needs to be efforts from education practitioners to find forms of learning that are in line with the development of today's children who live in the dimension of modernity. Sentra is an application that is oriented towards changing the morality, mental and intellectual of children for the better. The research method uses a qualitative approach, where data collection techniques use interview, observation, and documentation schemes. The research was carried out at Raudatul Athfal ABATA in the Karawang area of West Java. The collected data was then analyzed using a descriptive inductive analysis approach. The results of the study show that the learning process using seven central components 1) preparation, 2) beams, 3) art, 4) big roles, 5) natural materials, 6) body exercises, and 7) imtak, contributed significantly in strengthening cognitive aspects, psychomotor, and social interactions of children. In addition, the internalization of this method in the PAI learning process can bridge the formation of character towards religious students. The main key to the success of using this method is consistency of activity.